2018
DOI: 10.1016/j.jcou.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

CO2 as versatile carbonation agent of glycosides: Synthesis of 5- and 6-membered cyclic glycocarbonates and investigation of their ring-opening

Abstract: CO 2 as versatile carbonation agent of glycosides: Synthesis of 5-and 6-membered cyclic glycocarbonates and investigation of their ring-opening Item Type Article Authors Pati, Debasis; Feng, Xiaoshuang; Hadjichristidis, Nikos; Gnanou, Yves Citation Pati D, Feng X, Hadjichristidis N, Gnanou Y (2018) CO 2 as versatile carbonation agent of glycosides: Synthesis of 5-and 6membered cyclic glycocarbonates and investigation of their ringopening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…They already found that unprotected α-methyl D-glucopyranoside reacted with CO 2 , leading to water soluble oligoglycocarbonates [148]. Further studies from the same group showed that the reaction of CO 2 with cis vicinal hydroxy groups of sugars afforded instead 5-membered bicyclic glycocarbonates, in particular in the cis-2,3 or cis-3,4 positions of methyl α-D-mannopyranoside and methyl α-D-galactopyranoside, respectively (Scheme 12, Equations (2)-(4)) [149]. Also, a sixmembered bicyclic glycocarbonate was prepared from methyl 6-bromo-6-deoxy2,3-di-O-methyl α-D-galactopyranoside.…”
Section: Reactions Reported Inmentioning
confidence: 99%
“…They already found that unprotected α-methyl D-glucopyranoside reacted with CO 2 , leading to water soluble oligoglycocarbonates [148]. Further studies from the same group showed that the reaction of CO 2 with cis vicinal hydroxy groups of sugars afforded instead 5-membered bicyclic glycocarbonates, in particular in the cis-2,3 or cis-3,4 positions of methyl α-D-mannopyranoside and methyl α-D-galactopyranoside, respectively (Scheme 12, Equations (2)-(4)) [149]. Also, a sixmembered bicyclic glycocarbonate was prepared from methyl 6-bromo-6-deoxy2,3-di-O-methyl α-D-galactopyranoside.…”
Section: Reactions Reported Inmentioning
confidence: 99%
“…[136][137][138] Two more derivatives were later synthesized through the same method, i.e., selective protection and bromination of the 6-position followed by reaction with DBU and CO 2 in DMF. 157 By this method, the authors could synthesize cyclic carbonates from a D-mannose and a D-galactose, and polymerize them through ROP.…”
mentioning
confidence: 99%
“…In the same article, the authors report a procedure to generate 5-membered cyclic carbonates regioselectively from galactose and mannose that were only methylated at the anomeric position (Scheme 20a). 157 The simple one-step reaction involves CH 2 Br 2 to generate a productive leaving group in the hemi-car-bonate fragment that allows for subsequent ring-closure to yield the cyclic carbonate (Scheme 20b). 158 The procedure is selective for the formation of cis-5-membered carbonates, no trans-cyclic carbonates or 6-membered (even if they are cis in the case of galactose) were observed.…”
mentioning
confidence: 99%
“…[5] However, the lower reactivity of more bulky epoxides has been recently catching growing attention of the community for various reasons. First, the conversion of internal epoxides is particularly relevant in the context of the valorization of biomass such as terpenes, [6] fatty acids [7] and sugars: [8] most of these structures contain internal olefin groups that upon epoxidation serve as useful precursors for the preparation of their bio-carbonates. Second, cyclic epoxides such as cyclohexene and cyclopentene oxide have frequently been used as suitable monomers for polycarbonate formation and their coupling with CO 2 often served to benchmark the performance of novel catalysts.…”
Section: Introductionmentioning
confidence: 99%